River Pollution in Batang Tembesi as an Idea for Representational Printmaking Creation - Lia Handayani; Hamzah Hamzah; Ahmad Solihin (V-art: Journal of Fine Art, 2026)
The pollution of the Batang Tembesi River in Sarolangun Regency, Jambi Province, has become a significant environmental issue affecting both ecosystem quality and the livelihoods of local communities. Illegal gold mining activities, industrial waste from palm oil production, and domestic garbage have substantially altered the river’s water quality, which was once an essential source of life for the surrounding population. This phenomenon served as the primary inspiration for a representational printmaking work that visualizes the environmental condition of the Batang Tembesi River and fosters ecological awareness within the community. The artwork employs a representational approach, juxtaposing the beauty of the natural landscape with the irony of environmental degradation. The creative process follows Gustami’s three-stage method of exploration, design, and realization. The exploration stage involved field observations, interviews, and literature studies; the design stage consisted of developing alternative sketches; while the realization stage utilized the stencil technique with acrylic paint on canvas. The resulting artwork, titled Kilau di Atas Keruh (Shimmer Above the Murky Waters), measures 110 × 140 cm and depicts a panorama of the Beatrix Bridge and the Batang Tembesi River at sunset. The contrast between the landscape's visual beauty and the river's murky color symbolizes the ongoing ecological crisis. This work is expected to function as a medium for reflection, social criticism, and environmental education regarding the importance of preserving rivers as vital sources of community life